Systematic analysis of JmjC gene family and stress-response expression of KDM5 subfamily genes in Brassica napus - He,Xinghui; Wang,Qianwen; Pan,Jiao; Liu,Boyu; Ruan,Ying; Huang,Yong (PeerJ, 2021)
Background Jumonji C (JmjC) proteins exert critical roles in plant development and stress response through the removal of lysine methylation from histones. Brassica napus, which originated from spontaneous hybridization by Brassica rapa and Brassica oleracea, is the most important oilseed crop after soybean. In JmjC proteins of Brassica species, the structure and function and its relationship with the parents and model plant Arabidopsis thaliana remain uncharacterized. Systematic identification and analysis for JmjC family in Brassica crops can facilitate the future functional characterization and oilseed crops improvement. Methods Basing on the conserved JmjC domain, JmjC homologs from the three Brassica species, B. rapa (AA), B. oleracea (CC) and B. napus, were identified from the Brassica database. Some methods, such as phylogenic analysis, chromosomal mapping, HMMER searching, gene structure display and Logos analysis, were used to characterize relationships of the JmjC homologs. Synonymous and nonsynonymous nucleotide substitutions were used to infer the information of gene duplication among homologs. Then, the expression levels of BnKDM5 subfamily genes were checked under abiotic stress by qRT-PCR. Results Sixty-five JmjC genes were identified from B. napus genome, 29 from B. rapa, and 23 from B. oleracea. These genes were grouped into seven clades based on the phylogenetic analysis, and their catalytic activities of demethylation were predicted. The average retention rate of B. napus JmjC genes (B. napus JmjC gene from B. rapa (93.1%) and B. oleracea (82.6%)) exceeded whole genome level. JmjC sequences demonstrated high conservation in domain origination, chromosomal location, intron/exon number and catalytic sites. The gene duplication events were confirmed among the homologs. Many of the BrKDM5 subfamily genes showed higher expression under drought and NaCl treatments, but only a few genes were involved in high temperature stress. Conclusions This study provides the first genome-wide characterization of JmjC genes in Brassica species. The BnJmjC exhibits higher conservation during the formation process of allotetraploid than the average retention rates of the whole B. napus genome. Furthermore, expression profiles of many genes indicated that BnKDM5 subfamily genes are involved in stress response to salt, drought and high temperature.
Keywords: JmjC gene; Evolution; Histone lysine demethylases 5 subfamily; Abiotic stress; Brassica napus